A pretty kettle of fish: Contamination of fish from the Doce River basin after the world’s largest mining disaster and associated human health risks - Ajala-Batista, Larissa; Yamamoto, Flávia Yoshie [UNESP]; Padovan, Mayara; Scalon, Marina Corrêa; Grassi, Marco Tadeu; De Souza Abessa, Denis Moledo [UNESP]; Fávaro, Luís Fernando (Elsevier, 2025)
Four years after the Fundão mining tailings dam rupture (Mariana, Minas Gerais, Brazil), we assessed the bioaccumulation of metals (Al, Ba, Cd, Co, Cr, Cu, Fe, Li, Mn, Ni, Pb, Zn) and biliary polycyclic aromatic hydrocarbon (PAH) metabolites (2, 4, 5, and 6-ring) in fish from the Doce River Basin (DRB). We also identified human health risks from fish consumption and potential pollution sources. Fish were sampled from the upper, middle, and lower sectors during both the dry and wet seasons of 2019. Bioaccumulation of all metals was observed, with Cd, Cr, and Pb exceeding Maximum Tolerated Limits. The four PAH classes were detected, with petrogenic (2-ring) PAHs predominating at the highest concentrations. Likely pollution sources include agricultural activities, mining and industry operations, and sewage discharge. Risk assessments indicated that, as of 2019, consuming fish from the study area posed health risks, including both carcinogenic and non-carcinogenic effects, making it inadvisable.